2021
DOI: 10.1002/hpm.3398
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 prevention and control interventions: What can we learn from the pandemic management experience in Morocco?

Abstract: SUMMARY COVID‐19 is one of the worst outbreaks in infectious disease history. Through a succession of significant preventative and control interventions, Morocco has accumulated pandemic control experience. This study examines the available evidence on lessons learnt from the COVID‐19 pandemic management experience in Morocco. Social lockdown measures have helped restrain the exponential spread of new cases. These interventions appear to be reasonably successful. Their effectiveness must be confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In our study, we found no significant delay in diagnosis as reported by S. Aguiar Jr and al [ 9 ] and we found no change in the percentage of cancer diagnosed at the complication stage as found by Jian Cui and al [ 23 ] who also found a decrease in the number of asymptomatic cases this number is already extremely low in our country, as there is no national screening plan for digestive cancers [ 25 ].…”
Section: Discussionsupporting
confidence: 75%
“…In our study, we found no significant delay in diagnosis as reported by S. Aguiar Jr and al [ 9 ] and we found no change in the percentage of cancer diagnosed at the complication stage as found by Jian Cui and al [ 23 ] who also found a decrease in the number of asymptomatic cases this number is already extremely low in our country, as there is no national screening plan for digestive cancers [ 25 ].…”
Section: Discussionsupporting
confidence: 75%
“…More precisely, our analysis shows, in particular, that, while the epidemic growth is exponentially fast, by respecting a certain logistic growth, the epidemic might remain under control [6]. As a consequence, a non-negligible number of expenses can be saved.…”
Section: Introductionmentioning
confidence: 85%
“…To exemplify, we can consider the simple model ψ(S, Z) = S − Z = 0. In this case, we obtain Equation (6), which is linear. In a general situation, we obtain a nonlinear system, which must be solved by a convenient method to determine z.…”
Section: Numerical Methods For Uqmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature on COVID in Africa has mainly focused on prediction and modelling of the COVID epidemiology [ 5 11 ]. Many studies have analysed the capacity of health systems in Africa to respond to the pandemic, highlighting some positive experiences and strengths, such as technical leadership and multi-sectoral responses [ 12 ], positive effect of non-pharmaceutical interventions [ 13 , 14 ], implementation of Infection Prevention and Control (IPC) Committees [ 15 ], primary care approaches and benefits of technological innovations [ 16 ]. However, many studies also highlighted limited capacity to control the COVID pandemic [ 17 ], including poor testing capacity, under-funded health systems, lack of Intensive Care Unit beds, shortages of ventilators, personal protective equipment (PPE) for health workers, medical equipment, and medicines.…”
Section: Introductionmentioning
confidence: 99%